2020
DOI: 10.3390/ijerph17197081
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Beneficial Effects of the Immunomodulatory Glycan LNFPIII on Gut Microbiota and Health in a Mouse Model of Gulf War Illness

Abstract: The microbiota’s influence on host (patho) physiology has gained interest in the context of Gulf War Illness (GWI), a chronic disorder featuring dysregulation of the gut–brain–immune axis. This study examined short- and long-term effects of GWI-related chemicals on gut health and fecal microbiota and the potential benefits of Lacto-N-fucopentaose-III (LNFPIII) treatment in a GWI model. Male C57BL/6J mice were administered pyridostigmine bromide (PB; 0.7 mg/kg) and permethrin (PM; 200 mg/kg) for 10 days with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Giving mice butyrate during exposure with PB and permethrin resulted in increased butyrogenic bacteria, and decreased TLR4 activation 73 . Lacto‐N‐fucopentaose‐III is a glycan in human milk and also increased butyrate producer bacteria such as Butyricoccus and Ruminococcous in mice exposed to GW chemicals 74 . These treatments to mediate butyrate producing bacteria resulted in improved gut health and decreased inflammation.…”
Section: Animal Models Of Gwimentioning
confidence: 99%
See 2 more Smart Citations
“…Giving mice butyrate during exposure with PB and permethrin resulted in increased butyrogenic bacteria, and decreased TLR4 activation 73 . Lacto‐N‐fucopentaose‐III is a glycan in human milk and also increased butyrate producer bacteria such as Butyricoccus and Ruminococcous in mice exposed to GW chemicals 74 . These treatments to mediate butyrate producing bacteria resulted in improved gut health and decreased inflammation.…”
Section: Animal Models Of Gwimentioning
confidence: 99%
“…In clinical situation, changes in the types of diet can be easy for some people patients but hard for others. The development of supplements that contain various phytochemicals with anti-inflammatory effects 77,80,85 or milk glycan that improves gut microbiota profile 74 may help reducing the symptoms and/or can ameliorate the impacts of high-fat diet. Many studies have been done on the potential pharmaceutical treatments for GWI.…”
Section: High-fat Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the immune dysfunction in GWI, recent preclinical studies have explored the efficacy of several immune-targeted compounds that have shown some promising results ( Joshi et al, 2018 ; Kodali et al, 2018a ; Ribeiro et al, 2020 ; Shetty et al, 2020 ). In our studies, we have focused on one potent immunomodulatory and anti-inflammatory treatment, Lacto-N-fucopentaose III (LNFPIII), that may be an advantageous treatment option for GWI as demonstrated in two, chemically distinct GWI models ( Brown et al, 2021a , 2021b ; Carpenter et al, 2020 , 2021 ; Mote et al, 2020 ). LNFPIII is a Lewis(X)-containing immunomodulatory glycan found in human breast milk and on parasitic helminths that, to date, has had no documented adverse effects ( Atochina et al, 2008 ; Bhargava et al, 2012 ; Srivastava et al, 2014 ; Tundup et al, 2015 ; Zhu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%